A study of the relationship between general attention styles and academic achievement among students in physical activity and sports programs. - hamrouche, ahmed ridha; mhimdat, rachid (sports creativity, 2025)
Focusing attention is a crucial psychological skill for students in sports institutes. It is fundamental to the success of learning and training in all its forms. Distraction or lack of focus negatively impacts performance and achievement. The greater a student's ability to focus on the task at hand, the better their response. Even a slight lack of focus negatively affects performance and prevents students from achieving their full potential. Focus is a vital tool for enhancing athletes' abilities to observe things accurately and clearly. Athletes can demonstrate and develop their self-control and their ability to manage their surroundings, significantly increasing their focus under various circumstances, especially when they can adapt their behavior and feelings to the situation. This fosters mind-body harmony. Furthermore, controlling attention facilitates the transition from narrow to broad focus. Focus plays a significant role in academic achievement and is a key factor influencing skill performance. Schleppenberger emphasizes that focusing attention is a selective, organizing, and directive function of human consciousness, encompassing the relationship between the individual and the environment, as well as the connection between feeling and activity. From this perspective, we have chosen Some issues were raised regarding the process of attention in general, concerning the role of this quality in improving achievement in applied subjects for students in the field of physical activities and sports. What are the most important sources of distraction among students, and where is their attention directed? Does their mind wander towards factors in the environment surrounding the performance? Or is it directed towards past experiences? Or towards thinking about events related to the future? Preparing a student to be successful in his work is not only through academic qualification in his field of specialization. In this regard, Abdul Sattar Jabbar (2000) points out that when a stimulus is in the focus of attention, it means that an individual's attention is concentrated on it for a specific moment, and that other related subjects are on the periphery of attention. Focusing attention is important and plays a prominent role in all activities, especially those involving the physical element, such as the precision required in games and mathematics, which involve equipment and tools. Psychological state also plays a significant role in focusing attention. Abdul Sattar Jabbar states that psychological tension, negative emotional states, and the circumstances at the beginning and during a game can prevent complete focus, especially when an early goal is scored or a point is gained, leading to a sharp decrease in attention intensity. Furthermore, for a player to achieve optimal performance, all qualities and abilities must be integrated. In this regard, Muhammad Hassan Alawi (1975) says that a player's success or failure in demonstrating their best abilities and skills in athletic competition lies in the integration of these skills. Physical and motor skills, along with psychological skills such as relaxation and mental visualization (1), are crucial. General attention is a gateway to success in life, and acquiring and mastering general attention is no less important than academic qualification. Mayer and Salovey (1995) pointed out the possibility of improving students' academic achievement by developing their mental skills. This can be achieved by raising self-awareness, empathy, problem-solving, and emotional management within the educational environment. Therefore, the problem addressed in this study is the low academic performance of students in physical education and sports programs. Since there is a close relationship between the dimensions of general attention and academic performance, students with low attention spans will lack the ability to concentrate on their studies, negatively impacting their performance and creativity. Thus, it is essential to understand the nature and importance of attention in the educational environment, which will contribute to raising students' academic performance.